A Comparative Study between Extrovert and Introvert Personality on Speaking Achievement - Sinta Dewi Anggraeni; Semi Sukarni; Ismawati Ike Nugraeni (Scripta : English Department Journal, 2022)
The research's goals are to compare speaking achievement between extrovert and introvert personalities, and to see if there is a significant difference in speaking achievement between extrovert and introvert personality on the tenth grade at Senior High School 1 Pejagoan in the academic year 2020/2021. This study is classified as quantitative research with a non-experimental design. The population of this study is the tenth-grade students of SMA N 1 Pejagoan in the academic year 2020/2021. The researcher used a purposive selection strategy to select 60 students as her sample. The data was collected using a questionnaire, and the teacher provided the researchers with a copy of the student's speaking achievement as a document. There are 24 Yes/No questions in the form. To answer the issue and hypothesis statements, descriptive and inferential analysis techniques are used to analyze the data. The results of this study demonstrate that extrovert students' speaking achievement is in the "good" category, with a mean of 79.34, while introvert students' speaking achievement is also in the "good" category, with a mean of 77.50. Extroverts have higher English speaking scores at Senior High School 1 Pejagoan of the tenth grade. The result of hypothesis testing showed that the z-value (2526) computation result is higher than the ztable (1.96). Because Sig (2- tailed) is less than 0.05 (0.0070.05), Ha is accepted and Ho is rejected. Furthermore, it can be concluded that there is a significant difference in speaking achievement between extrovert and introvert students in the tenth grade of SMA N 1 Pejagoan in the academic year 2020/2021.